Tingkat stres pengasuhan pada orang tua selama masa pandemi coronavirus disease (Covid-19) - Ikeu Nurhidayah; Annisa Nurbaiti Rahmah; Adelse Prima Mulya; Nur Oktavia Hidayati (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: The coronavirus disease (COVID-19) pandemic has had an impact on various fields, including families, which caused children experiencing changes in their activities, as well as being at risk of developing developmental disorders, so the role of parenting is very important. Changes that occur during the pandemic can cause parenting stress on parents and affect the parenting given to children.Purpose: To identify the level of parenting stress in parents during the Coronavirus Disease (COVID-19) pandemic.Method: A quantitative with a descriptive design and consecutive sampling technique and uses the Parental Stress Scale research instrument. This research was conducted in one of the housing estates located in Cileunyi District, east of Bandung Regency. The population in this study were parents with children aged 0-18 years who lived in the Villa Padjajaran Permai Complex, totaling 84 families with a sample of 129 parents (65 fathers and 64 mothers). The data analysis used was descriptive univariate with low, medium, and high parenting stress categories.Results: Showing that parenting stress in the low category was 89.9% and the parenting stress was in the moderate category at 10.1%. The aspects that affect parents the most are their reduced time and flexibility, and the difficulty of balancing various responsibilities.Keywords: Covid-19; Pandemic; Parenting; StressPendahuluan: Pandemi coronavirus disease (COVID-19) memberikan dampak di berbagai bidang, termasuk keluarga yang mengakibatkan anak mengalami perubahan aktivitas, serta berisiko mengalami gangguan perkembangan, sehingga peran pengasuhan orang tua menjadi sangat penting. Perubahan yang terjadi selama pandemi dapat menimbulkan stress pengasuhan pada orang tua serta memengaruhi pola asuh yang diberikan kepada anak.Tujuan: Untuk mengidentifikasi tingkat stres pengasuhan pada orang tua selama masa pandemi Coronavirus Disease (COVID-19).Metode: Penelitian kuantitatif dengan desain deskriptif dan teknik sampling consecutive sampling serta menggunakan instrumen penelitian Parental Stress Scale. Penelitian ini dilakukan di salah satu perumahan yang berada pada Kecamatan Cileunyi wilayah timur dari Kabupaten Bandung. Populasi dalam penelitian ini adalah orang tua dengan anak usia 0-18 tahun yang bertempat tinggal di Komplek Villa Padjajaran Permai yang berjumlah 84 KK dengan sampel berjumlah 129 orang tua (65 ayah dan 64 ibu). Analisis data yang digunakan adalah deskriptif univariat dengan kategori hasil stres pengasuhan rendah, sedang, dan tinggi.Hasil: Menunjukkan stres pengasuhan berkategori rendah sebesar 89.9% dan stres pengasuhan berkategori sedang sebesar 10,1%. Aspek yang paling mempengaruhi orang tua adalah waktu dan fleksibilitas mereka berkurang, serta kesulitan menyeimbangkan berbagai tanggung jawab.